THE THEORY OF LEXICAL CHANGE IN ENGLISH LANGUAGE - Sultanbekova, A.A. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
The article is dedicated to the role of changes in lexical corps in films. It is devoted to the study of changes in the vocabulary, how time affects the vocabulary of films of different times.
Keywords: diachronic linguistics; vocabulary; phraseology; linguistics; lexicology; language; meaning; applied lexicology; semantic shift; broadening; narrowing; amelioration; pejoration